Paul’s Eschatological Ethics for the Global South - Yimenu Adimass Belay (African Theological Journal for Church and Society)
The article argues that Paul’s exhortation to live a higher ethical life in Romans 13:11-14 is confirmed, given the eschatological view of believers’ final salvation. Paul’s eschatological perspective in Romans indicates the glorification of believers despite the current suffering that stands against Christian life (Rom. 8:28-36; 12:2). According to Paul, the path to glorification is through suffering, and the motivation for perseverance and obedience to the higher ethical life is the eschatological expectation and the final salvation of believers (Rom. 5:1-11; 8:18-25). Paul’s argument for the relation between eschatology and ethics seems clearly stated in 13:11-14, insisting on moral obligation in view of eschatology (Keck 2005:333-334). Therefore, Paul’s view of eschatological ethics in this text is vital for the higher ethical life to be applied in the church of Africa and beyond. The study uses a socio-rhetorical analysis as a fruitful methodology to explore how Paul’s use of eschatological expectation is motivational for a higher standard of Christian life in the presence of challenges and suffering in the first century. This could teach the way to live a Christian ethical life in the presence of contemporary challenges in Africa and beyond. With the aim of articulating the role of eschatology for Christian ethical life in Paul in the designated text, the article attempts to review some related literature, considering the history of research. Romans 13:11-14 is analysed using socio-rhetorical analysis to establish Paul’s main message to attest to how ethics is connected with the eschatological expectation. Paul’s view of eschatology and ethics in this text shows the link between eschatology and ethics. Therefore, the article argues that the relationship between eschatology and ethics in Romans 13:11-14 is essential, showing how eschatological ethics is motivational and can teach an ethical Christian life for the contemporary African church and beyond.